2009
DOI: 10.1261/rna.1652709
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional studies of the Thermus thermophilus 16S rRNA methyltransferase RsmG

Abstract: The RsmG methyltransferase is responsible for N 7 methylation of G527 of 16S rRNA in bacteria. Here, we report the identification of the Thermus thermophilus rsmG gene, the isolation of rsmG mutants, and the solution of RsmG X-ray crystal structures at up to 1.5 Å resolution. Like their counterparts in other species, T. thermophilus rsmG mutants are weakly resistant to the aminoglycoside antibiotic streptomycin. Growth competition experiments indicate a physiological cost to loss of RsmG activity, consistent w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 54 publications
1
28
0
Order By: Relevance
“…In spite of participation of the 530 loop in the decoding process being clear, the precise role of the m 7 G527 modification has remained elusive. Loss of RsmG activity confers low-level streptomycin resistance and inexplicably prompts the appearance of high-level streptomycin resistance mutations in the S12-encoding gene, rpsL (Nishimura et al 2007a,b;Okamoto et al 2007;Gregory et al 2009;Wong et al 2011). Moreover, the effects of rsmG mutations on bacterial fitness and translational accuracy have been reported as being variable, depending on the bacterial species (Nishimura et al 2007b;Okamoto et al 2007;Gregory et al 2009;Ochi et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In spite of participation of the 530 loop in the decoding process being clear, the precise role of the m 7 G527 modification has remained elusive. Loss of RsmG activity confers low-level streptomycin resistance and inexplicably prompts the appearance of high-level streptomycin resistance mutations in the S12-encoding gene, rpsL (Nishimura et al 2007a,b;Okamoto et al 2007;Gregory et al 2009;Wong et al 2011). Moreover, the effects of rsmG mutations on bacterial fitness and translational accuracy have been reported as being variable, depending on the bacterial species (Nishimura et al 2007b;Okamoto et al 2007;Gregory et al 2009;Ochi et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Loss of RsmG activity confers low-level streptomycin resistance and inexplicably prompts the appearance of high-level streptomycin resistance mutations in the S12-encoding gene, rpsL (Nishimura et al 2007a,b;Okamoto et al 2007;Gregory et al 2009;Wong et al 2011). Moreover, the effects of rsmG mutations on bacterial fitness and translational accuracy have been reported as being variable, depending on the bacterial species (Nishimura et al 2007b;Okamoto et al 2007;Gregory et al 2009;Ochi et al 2009). We recently found that a null rsmG mutation produces an error-prone phenotype in certain genetic backgrounds, which suggests that modification m 7 G527 is important for ribosomal accuracy and that pleitropy may explain, at least partially, the observed variability (A Benítez-Páez, M Villarroya, and M-E Armengod, in prep.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations